KAJIAN KRIMINOLOGI PEREDARAN NARKOTIKA (SEBUAH STUDI DI KABUPATEN ACEH TIMUR) - Muammar, Muammar (JURNAL AL-IJTIMAIYYAH, 2019)
The impact of globalization has penetrated throughout the civilization of the nations of the world, running so fast. Especially very influential on changes in various lines of life. Related to this is the issue of increasing narcotics abuse and narcotics illicit trafficking which has created conditions that have hindered the development process and weakened civilization. Eradication of narcotics distribution is a national problem, because it has a negative impact that can damage and threaten the lives of the people, nation and state and can hamper the national development process. The rise of narcotics abuse does not only occur in big cities, but has reached small cities in all ten regions of the Republic of Indonesia, including East Aceh Regency. The increasingly diverse lifestyle of the people due to the influence of globalization also contributes to the increasing circulation of narcotics in East Aceh District. This certainly must receive serious attention, because if we look at what is happening in East Aceh District and several other regions in Indonesia, the crime of narcotics distribution from time to time always increases which in the end is increasingly unsettling the community, so before these things increase In East Aceh District, an effective solution must be found to eradicate it. Factors that cause a person to commit a narcotics crime in East Aceh Regency are due to economic factors where a person needs money to live and the difficulty of getting work, family environmental factors, social environmental factors and availability / lack of supervision factors. Efforts in tackling narcotics circulation in East Aceh district involve many parties, including: firstly, pre-emptive efforts by providing counseling in the community and schools about narcotics carried out by the police in tackling narcotics crime in East Aceh District. Second, preventive measures (prevention) by conducting raids and patrols routinely, providing oversight of the association and positive activities carried out by the police, prosecutors, religious leaders, community leaders and youth organizations. The third repressive effort (action) which aims to provide a deterrent effect on the perpetrators of drug trafficking crimes involving all law enforcement officials ranging from the Police, Attorney and District Courts and Detention Houses.Keywords: Crimonology, Narcotics Circulation.